Imaging characteristics of lumbar spine lesions and their associations in patients with axial spondyloarthritis - Nguyen, Hoang Minh; Nguyen, Hoang Thanh Van; Le, Thi Hong Van (Tạp chí Y Dược Huế, 2026)
Background: Axial spondyloarthritis (axSpA) is a chronic inflammatory disease with heterogeneous clinical manifestations. Lesions of the sacroiliac joints and the lumbar spine play an important role in functional limitation in patients with axial spondyloarthritis. Therefore, this study aimed to evaluate lumbar spine lesions on imaging and to investigate their associations with clinical characteristics and disease activity. Methods: A cross-sectional descriptive study was conducted on 45 patients with axial spondyloarthritis treated at the Department of General Internal Medicine – Endocrinology – Rheumatology, Hue University of Medicine and Pharmacy Hospital, from 2/2023 to 8/2024. Results: A total of 73.3% of patients had an ASDAS-CRP score > 3.5, indicating very high disease activity. On radiography, abnormalities related to lumbar spine involvement were observed in 6/32 cases, among which 5 cases showed tangential osteophytes and Romanus lesions, accounting for 15.6%. Active lesions of the lumbar spine on MRI were detected in 13/45 patients (28.9%), with vertebral corner inflammation being the most common finding. Age, disease duration, CRP levels, BASDAI, and ASDAS-CRP were significantly associated with the number of lesions detected on MRI. Conclusion: Lumbar spine lesions on MRI were identified in 28.9% of patients with axial spondyloarthritis, with a median disease duration of 2 years. Only 6/32 cases showed abnormalities related to axial spondyloarthritis on X-ray. Lumbar spine involvement was associated with age, disease duration, CRP levels, and disease activity indices including BASDAI and ASDAS-CRP.